KALIMAT BAHASA SIANG - Sigiro, Elisten Parulian (SUAR BETANG, 2018)
The method used in this research is descriptive qualitative method because the method and technique of this research is fact findings that exist in the field as it is. Problem solved in this research are the problems associated with the system language syntax Siang. Thus, this study generally aims to collect data, analyze, and describe in depth and detail the syntax of the language system Siang. The results of this study indicate that the constituents of sentences in Siang include core constituents and constituents periphery. Common constituent sequence is the subject-predicate-object or simply the subject and predicate. Based on capital characteristics, characteristics, types, and patterns of sentences in Siang include declarative sentence, imperative and interrogative. Based on the characteristics of the predicate sentence in Siang  include 1) an active sentence consisting of active transitive sentences, active bitransitif, active intransitive transitive and intransitive sentences, 2) stative sentence consists of stative sentences ejuatif, locative, descriptive, eksistensional, and possessive. Characteristics, types and patterns Siang language sentence by sentence with diathesis include diathesis active and passive voice